Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Créer, écrire et informer en tant que féministes - Institut de recherches et d'études féministes
Explorons ensemble des pistes de réflexion pour utiliser les outils féministes à toutes les étapes de la production artistique et culturelle. Que ce soit dans le milieu du journalisme, de l'édition et la création littéraire, de l'humour ou de l'audiovisuel, les intervenantes partagent des outils d'analyse pour repérer les biais patriarcaux et et des stratégies pour créer des pratiques plus libératrices. Avec: Audrey Boutin, Stéfany Boisvert, Claire Ross, Mélissa Thériault, Louise Richer, Madioula Kébé Kamara, Ariane Gibeau, Katia Belkhodja, Maude Goyer Épisode enregistré durant la Foire féministe de l'IREF (27, 28 février et 1er mars 2025 - https://sites.grenadine.uqam.ca/sites/dsj/fr/foire-feministe-feministes-dans-la-cite). Ecrit par Nerea Aizpuru et Juliette Chevet, monté par Juliette Chevet. Avec le soutien financier du CRSH.
Keywords: 2020-2029; approches et analyses; arts; communication; discipline; foire féministe; justice sociale; médias; patriarcat; périodes historiques; québec; régions géographiques; systèmes d'oppressions; études littéraires

Être féministe et objectifier son propre corps : les autoportraits d'Hannah Wilke - Institut de recherches et d'études féministes
Est-ce que c'est féministe de se mettre nue devant une caméra ? Comment peut-on jouer avec la caméra jusqu'à reprendre pouvoir sur notre image ? Amélie Fontaine-Dupont nous partage ses résultats de recherche sur l'artiste Hannah Wilke et montre comment l'auto-objectification sexuelle peut être une posture féministe et permettre d’approfondir la réflexion sur la culpabilisation et la répréhension des femmes qui font usage de leur corps et de leur sexualité à des fins d’émancipation. Biographie: Amélie Fontaine-Dupont est étudiante à la maîtrise en histoire de l'art à l'UQAM et détient un baccalauréat en histoire de l'art de l'Université Laval. S’intéressant autant aux études féministes qu’à l’art contemporain, ses recherches actuelles portent sur l'auto-objectification sexuelle comme forme d’agentivité et d’activisme féministe dans les œuvres performatives de l'artiste états-unienne Hannah Wilke. Amélie est membre étudiante de l'Institut de recherches et d'études féministes de l’UQAM et du Réseau québécois en études féministes. Elle occupe également le poste de responsable des communications de l'Association des cycles supérieurs en histoire de l'art de l'UQAM. En parallèle à ses études, elle travaille à la Galerie de l'UQAM et intervient ponctuellement en tant que médiatrice culturelle à l'occasion d'évènements artistiques et d’expositions. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Rajae Anys et Juliette Chevet. Ecrit et monté par Juliette Chevet. Avec le soutien financier du CRSH
Keywords: 1900-1999; 1970-1979; 1980-1989; amérique; approches et analyses; arts; corps; discipline; foire féministe; histoire de l'art; militance; patriarcat; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis